Identification of NY-ESO-1157–165 Specific Murine T Cell Receptors With Distinct Recognition Pattern for Tumor Immunotherapy - Zhang, Helin; Sun, Meng; Wang, Jie; Zeng, Bin; Cao, Xiaoqing; Han, Yi; Tan, Shuguang; Gao, George F. (Frontiers in Immunology, 2021)
New York esophageal squamous cell carcinoma 1 (NY-ESO-1) is a promising target for T-cell receptor-engineered T cell (TCR-T) therapy, and targeting the human leukocyte antigen (HLA)-A2 restricted NY-ESO-1157−165 epitope has yielded remarkable clinical benefits in the treatment of multiple advanced malignancies. Herein, we report the identification of two NY-ESO-1157−165 epitope-specific murine TCRs obtained from HLA-A*0201 transgenic mice. NY-ESO-1157−165 specific TCRs were isolated after vaccinating HLA-A2 transgenic mice with epitope peptides. HZ6 and HZ8 TCRs could specifically bind to NY-ESO-1157−165/HLA-A2 and were capable of cytokine secretion with engineered Jurkat T cells and primary T cells upon recognition with K562 target cells expressing the single-chain trimer (SCT) of NY-ESO-1157−165/HLA-A2. The reactivity profiles of the HZ6 and HZ8 TCRs were found to be distinct from one another when co-cultured with K562 target cells carrying alanine-substituted NY-ESO-1157−165 SCTs. The binding characterization revealed that the recognition pattern of the HZ6 TCR to NY-ESO-1157−165/HLA-A2 was substantially different from the widely used 1G4 TCR. These findings would broaden the understanding of immunogenicity of the NY-ESO-1157−165, and the two identified TCRs may serve as promising candidates for the future development of TCR-T therapy for tumors.